O dentro é o fora : a criação nascente no pensamento de Lygia Clark - Magalhães, Thaís Fernanda Rocha (2024)
This thesis proposes a reflection on the inventive process of Brazilian artist Lygia Clark. I examine the experiments, materials, recurring expressions and the artist's effort to make a journey between the work of art, up to the scope of the gaze, and the sensorial object with potentially therapeutic capabilities. This crossing, which constitutes an embryonic process, is part of a context of ruptures with the traditional ways of conceiving the artistic experience and its circulation paths. I bring the artist's elaborations closer to the notions of aesthetic paradigm and creation in a nascent state suggested by Félix Guattari (1992). These approaches aim to set into motion modes of enunciation inherent to creative action. Along this path, a hypothesis for this reflection, based on the principle of nascent creation, is that, in Lygia Clark's trajectory, there is a thought in art that aims at the programmatic transgression of the limits of the work. This process opened fertile territory for the emergence of different modes of recreation and reception of works of art. This hypothesis dialogues with Suely Rolnik's (2018) reading of the larval worlds left by Lygia Clark for contemporary art. Given this articulation, I seek to demonstrate the strength of the artist's thought that remains a reference for experimenting with languages and building environments for artistic creation in all its potential.